3D-Accuracy Improvements for TDoA Based Wireless Local Positioning Systems - Eickhoff, Ralf; Ellinger, Frank; Mosshammer, Ralf; Weigel, Robert; Ziroff, Andreas; Huemer, Mario (IEEE GLOBECOM Workshops, 2008 (WMSN), 2008)
Local positioning systems significantly enhance the value of wireless sensor networks (WSN). This paper gives an overview of local positioning system topologies for WSNs of the European project RESOLUTION, which operate in the unlicensed ISM band at 5.8 GHz with 150 MHz bandwidth and allowed 25 mW effective isotropic radiated transmit power. The achievable 3D-localization accuracy is analyzed with respect to the performance of the designed hardware components and the indoor environment. It is further shown that accuracy as a primary attribute of local positioning systems also affects secondary quality-of-service (QoS) features such as update-rates or latency. This investigation allows an optimization of both attributes simultaneously, primary and secondary QoS aspects.
elib2cris::1512001600,eickhoff2008